Analisis Pelaksanaan Kurikulum 2013 Pada Pembelajaran Peminatan Di SMA Negeri Kota Ternate - Usman, Widyasari; Poerwanti, Endang; Hudha, Atok Miftachul (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: The subject of specialization can help the development of abilities possessed by students. Specifically, specialization subjects can be followed according to students' talents and interests. This study aims to describe (1) the implementation of the 2013 curriculum policy in specialization learning in Senior High School 1 Ternate. (2) differences in specialization management models are applied in Senior High School 1 Ternate. And (3) constraints and solutions in the implementation of specialization learning in Senior High School 1 Ternate. This research was conducted with a descriptive qualitative approach. Sources of data and information from three curriculum subjects and nine specialization subject teachers from each of the three schools. The results showed that (1) the implementation of the 2013 curriculum in specialization learning in Senior High School 1 Ternate was byÂ Minister of Education and Culture Regulations number 69 of 2013 and schools only make policies based on the central government and adjust teaching hours and based on specialization manuals and cross-interests from the Ministry of Education and Culture in 2016 and 2017. (2) There are some differences from specialization management models such as specialization mechanisms/procedures in each school have different stages. (3) Obstacles in the implementation of specialization learning in Senior High School 1 Ternate include (a) constraints from teachers; (b) constraints in choosing teaching methods; (c) constraints from students; (d) the constraints of using learning resources; (e) facilities and infrastructure. The solution is that the teacher chooses the right teaching method and can improve the competency of the studentsKeywords: Learning, Specialization Subjects, 2013 CurriculumÂ Abstrak: Diberlakukan mata pelajaran peminatan dapat membantu pengembangan kemampuan yang dimiliki oleh siswa. Secara khusus mata pelajaran peminatan dapat diikuti sesuai bakat dan minat siswa. Penelitian ini bertujuan untuk mendeskripsikan tentang (1) pelaksanaan kebijakan kurikulum 2013 pada pembelajaran peminatan di SMA Negeri Kota Ternate. (2) perbedaan model manajemen peminatan diterapkan di SMA Negeri Kota Ternate. Dan (3) kendala dan solusi dalam pelaksanaan pembelajaran peminatan di SMA Negeri Kota Ternate.Penelitian ini dilakukan dengan pendekatan kualitatif deskriptif. Sumber data dan informasi dari tiga masing-masing wakasek kurikulum dan sembilan guru mata pelajaran peminatan dari tiga masing-masing sekolah. Hasil penelitian menunjukkan bahwa (1) pelaksanaan kurikulum 2013 pada pembelajaran peminatan di SMA Negeri Kota Ternate sudah sesuai dengan Permendikbud No. 69 Tahun 2013 dan sekolah hanya membuat kebijakan berdasarkan dari pemerintah pusat dan menyesuaikan jam mengajar serta berdasarkan buku pedoman peminatan dan lintas minat dari Kemendikbud tahun 2016 dan 2017. (2) Terdapat beberapa perbedaan dari model-model manajemen peminatan seperti mekanisme/prosedur peminatan di setiap sekolah memiliki tahapan-tahapan berbeda. (3) Kendala dalam pelaksanaan pembelajaran peminatan di SMA Negeri Kota Ternate meliputi (a) kendala dari guru; (b) kendala memilih metode mengajar; (c) kendala dari siswa; (d) kendala menggunakan sumber belajar; (e) sarana dan prasarana. Solusi yang dilakukan yaitu guru memilih metode mengajar tepat dan dapat meningkatkan kompetensi peserta didikKata kunci: Pembelajaran, Mata Pelajaran Peminatan, Kurikulum 2013